2019
DOI: 10.1055/s-0039-1691069
|View full text |Cite
|
Sign up to set email alerts
|

A Green Nanopalladium-Supported Catalyst for the Microwave-Assisted Direct Synthesis of Xanthones

Abstract: We report an efficient, selective, rapid and eco-friendly protocol for the one-step synthesis of a small xanthone library via an intermolecular catalytic coupling from readily available salicylaldehydes and 1,2-dihaloarenes under ligand-free conditions. To achieve this advantageous direct annulation, we used a novel recoverable palladium nanocatalyst supported on a green biochar under microwave irradiation. Unlike other existing palladium-based approaches, our synthetic strategy showed a greater operational si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Another recent approach to synthesize xanthone derivatives was reported by Steingruber et al, employing salicylaldehyde and dibromobenzene derivatives using palladium nanoparticles. High yield (up to 88% yield), as well as high regioselectivity reaction, were achieved within 30 min reaction time in which the nanopalladium catalyst can be used up to four consecutive cycles without losing its activity [84]. Figure 7 shows the recent examples of the synthesis of xanthone derivatives using MAOS technique.…”
Section: Synthesis Of Xanthone Derivativesmentioning
confidence: 99%
“…Another recent approach to synthesize xanthone derivatives was reported by Steingruber et al, employing salicylaldehyde and dibromobenzene derivatives using palladium nanoparticles. High yield (up to 88% yield), as well as high regioselectivity reaction, were achieved within 30 min reaction time in which the nanopalladium catalyst can be used up to four consecutive cycles without losing its activity [84]. Figure 7 shows the recent examples of the synthesis of xanthone derivatives using MAOS technique.…”
Section: Synthesis Of Xanthone Derivativesmentioning
confidence: 99%
“…A rapid and con- venient ligand-free alternative was later reported for this direct annulation using a recoverable palladium nanocatalyst supported on a green biochar under microwave irradiation, with a drastic reduction in reaction times. 127 This eco-friendly strategy proceeded in very good yields (54-88%) and with high regioselectivity for a scope of 20 xanthone derivatives.…”
Section: Synthesis Of Xanthones By Condensation Of a Salicylaldehyde mentioning
confidence: 94%
“…Aside the o-acylation of phenols with 2-substituted aldehydes, the xanthone core can also be constructed through a selective palladium-catalysed acylation/nucleophilic aromatic substitution (S N Ar) approach of salicylaldehyde derivatives with aryl halides (Scheme 3). 127,128 The first methodology reported consisted of the use of a bulky electron-rich trialkylphosphine ligand, n-BuPAd 2 , which prevents the decomposition of the palladium catalyst, observed with the use of other ligands. 128 The scope of the reaction was extended to 22 different xanthones (41-81% yield); however, only activated salicylaldehydes were tolerated, long reaction times (12 h) were needed, and it was impractical to recover and reuse the catalyst.…”
Section: Synthesis Of Xanthones By Condensation Of a Salicylaldehyde mentioning
confidence: 99%
“…Gerbino and co-workers reported the synthesis and characterization of efficient, novel and recyclable PdNPs anchored on green biochar (PdNPs/BC) through a precipitation-reduction method employing the use of PdCl 2 as the precursor, biochar as the support, and the pyrolytic product of lignocellulosic biomass. 306 The were employed in the microwave-mediated, ligand-and additive-free, regioselective synthesis of xanthones (136b) from substituted salicylaldehydes (21f) and o-bromo haloarenes (82l) (Scheme 168). The PdNPs/BC NCs were separated by ltration and reused for up to four cycles in 88-82% yield, where they maintained their initial activity, as conrmed by AAS and XRD.…”
Section: Pdnp-catalyzed Synthesis Of Heterocyclesmentioning
confidence: 99%
“…Kaushik et al reported that commercially available zinc oxide nanoparticles (ZnO NPs) as a Lewis acid catalyzed the synthesis of 1,2-dihydro-1-arylnaphtho[1,2-e][1,3]oxazine-3-ones (305) and 14-substituted-14H-dibenzo [a,j]xanthenes (306,Scheme 195) under solvent-free conditions. 357 The synthesis of 305 was achieved from substituted benzaldehyde (21a) and urea (22b) following the sequential addition of b-naphthol (111d) in 76-94% yield, whereas 306 was synthesized from substituted benzaldehyde (21a) and b-naphthol (111d) at 120 C via random addition in 80-92% yield (Scheme 196).…”
Section: Znnp-catalyzed Synthesis Of Heterocyclesmentioning
confidence: 99%